2012
DOI: 10.1016/j.ygyno.2012.07.124
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the feasibility and acceptability of a Web-based, electronic patient-reported outcome system in assessing patient recovery after major gynecologic cancer surgery

Abstract: Purpose The purposes of this study are to evaluate the feasibility of capturing patient-reported outcomes (PROs) electronically and to identify the most common distressing symptoms in women recovering from major gynecologic cancer surgery. Methods This was a prospective, single-arm pilot study. Eligible participants included those scheduled for a laparotomy for presumed or known gynecologic malignancy. Patients completed a Web-based “STAR” (Symptoms Tracking and Reporting for Patients) questionnaire once pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 14 publications
2
91
0
Order By: Relevance
“…The use of Internet and mobile devices that allow patients to report symptoms as they occur could provide additional insight into the timing and severity of symptoms. 1618 …”
Section: Discussionmentioning
confidence: 99%
“…The use of Internet and mobile devices that allow patients to report symptoms as they occur could provide additional insight into the timing and severity of symptoms. 1618 …”
Section: Discussionmentioning
confidence: 99%
“…The patients, study design, and online platform were previously described in a pilot report on the feasibility and acceptability of this Web-based system [7]. English-speaking patients 18 years of age and older, who were scheduled to undergo laparotomy for presumed or known gynecologic malignancy, were recruited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Our previously published pilot study suggested that the use of a Web-based system to capture PROs is feasible and highly acceptable by patients in the acute postoperative period after major gynecologic surgery[7]. The objectives of this study were to update the experience of these patients, and to assess patient and provider satisfaction and feedback regarding the system.…”
Section: Introductionmentioning
confidence: 99%
“…Th ese conditions often are not considered really compromising by attending physicians from a prescriptive point of view, but prove to be highly invalidating [21][22][23] from the point of view of patients. In particular, highly signifi cant results are achieved concerning the presence of alteration of bowel function, pain, anxiety and depression, malaise, fatigue and abnormal sleep-rest pattern 8,24 , as such toxicities, very frequently suggested by patients, tend to be underestimated and undervalued by operators [25][26][27][28][29] ( Table 2, Fig. 2).…”
Section: Resultsmentioning
confidence: 99%